The homeostasis solution – Mechanical homeostasis in architecturally homeostatic buildings. (15th January 2016) - Wang, Lin-Shu; Ma, Peizheng
Graphical abstract: Highlights: Architectural homeostatic buildings (AHBs) make sense because of the laws of physics. However, high efficiency can be obtained only with AHBs and equipment considered as systems. Mechanical homeostasis facilitates AHB-equipment system synergy with heat extraction. Entropically speaking a building needs neither energy nor a fixed amount of heat, but its homeostatic existence. Homeostatic buildings can reduce building energy consumption from 80% to 90%. Abstract: We already know, for energy-saving potential, the necessary architectural features in well-designed buildings: high performance building envelope, sufficient interior thermal mass, and hydronic-network activated radiant surfaces for cooling and heating. Buildings with these features may be referred to as architecturally homeostatic buildings (AHBs); such a building-system is thermally semi-autonomous in the sense that its temperature variation stays within a certain range even without conditioning equipment, and, with conditioning equipment in operation, its thermal regulation is handled by its hydronic heat-distribution-network for controlling the temperature level of the building. At the present time conventional HVAC equipment is used for maintaining the heat-distribution-network: this arrangement, however, has resulted in great energy saving only for AHBs with accessible natural water bodies. In operation of general AHBs, a case is made here for a new kind of mechanical equipment having the attribute of mechanical homeostasis (MH). MH is a new energy transformation concept in a triadic framework. Superlative energy efficiency is predicted as a result of combined improvements in higher triadCOP s and lower total (inducted + removed) heat rates—evincing existence of synergy in architectural and mechanical homeostasis, which together will be referred to as the homeostasis solution.